Pengaruh Pelatihan, Tunjangan, Dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. Sumber Alfaria Trijaya, Tbk - Albertus Bintang Pramudya; Dimas Syahlevi; Roy Ade Melandry; Yesika Putri Kasi (CV. ITTC INDONESIA, 2025)
This study aims to explore and understand the influence of training, employee benefits, and the work environment on the performance of employees at PT. Sumber Alfaria Trijaya, Tbk (Alfamart) using a qualitative descriptive approach. In the context of the increasingly competitive retail industry, companies must continuously improve the quality of their human resources. Therefore, this research focuses on how training programs enhance employee competencies, how benefits affect motivation and loyalty, and how physical and non-physical work environments impact employee comfort and productivity. Data were collected through in-depth interviews, direct observations in the workplace, and document analysis. The findings indicate that ongoing and relevant training significantly improves individual skills and work efficiency. Benefits such as performance incentives and transportation allowances serve as strong motivators that enhance job satisfaction and retention. Meanwhile, a supportive work environment—both physically safe and socially harmonious—creates a positive workplace culture that fosters higher employee engagement and productivity. These three factors are interrelated and collectively influence employee performance. The study suggests that management should emphasize a holistic and human-centered HR strategy to optimize employee performance and organizational success.